Genomic characterization of triple-carbapenemase-producing Acinetobacter baumannii. Issue 4 (18th December 2021) - Oinuma, Ken-Ichi; Suzuki, Masato; Sakiyama, Arata; Tsubouchi, Taishi; Saeki, Kozo; Sato, Kanako; Niki, Mamiko; Yamada, Koichi; Shibayama, Keigo; Kakeya, Hiroshi; Kaneko, Yukihiro
Abstract: Objectives: To characterize Acinetobacter baumannii OCU_Ac16a, a clinical isolate co-harbouring three acquired carbapenemase genes, bla NDM-1, bla TMB-1, and bla OXA-58, and assess the clinical significance of so-called multiple-carbapenemase producers. Methods: OCU_Ac16a and its close relative, OCU_Ac16b, which lacks the bla NDM-1, were isolated from sputum cultures of a patient at Osaka City University Hospital. We subjected these strains to whole-genome analysis, particularly focusing on the genetic context of each carbapenemase gene. The transmissibility and functionality of each carbapenemase gene were analysed by conjugation and transformation experiments and antimicrobial susceptibility tests. Results: bla TMB-1 was located in a class 1 integron on the chromosome, whereas bla NDM-1 and bla OXA-58 were found on plasmids named pOCU_Ac16a_2 and pOCU_Ac16a_3, respectively. pOCU_Ac16a_2 (which exhibited highly efficient self-transmissibility) and pOCU_Ac16a_3 (which did not show transmissibility but could be introduced into another A. baumannii strain via electroporation) could both confer carbapenem resistance (MICs ≥512 and ≥32 mg/L, respectively) on the recipient strain. The functionality of bla TMB-1 was evident from the high resistance of OCU_Ac16b to ceftazidime and cefepime (MICs ≥256 and 48 mg/L, respectively), and the high resistance of OCU_Ac16a to cefiderocol (MIC 32 mg/L) could be explained by the additive effect of bla NDM-1 and bla TMB-1 . Conclusions: Our data revealed the genomic organization of OCU_Ac16a and demonstrated that all the carbapenemase genes are functional, each contributing to the extremely high broad-spectrum resistance of OCU_Ac16a to β-lactams. As multiple-carbapenemase producers can be serious health threats as drug-resistant pathogens and disseminators of carbapenemase genes, close attention should be paid to their emergence.